Mineral composition, quality and internal breakdown of 'Fuji' apples in different rootstocks during controlled atmosphere storage Composição mineral, qualidade e degenerescência de polpa de maçãs 'fuji' em diferentes porta-enxertos durante armazenamento em atmosfera controlada - Correa T.R.* (2012)
This study was carried out to evaluate the effects of three rootstocks on mineral composition of 'Fuji' apples, as well as on their, quality and incidence of internal breakdown in two controlled atmosphere (CA) conditions. Fruits harvested from trees with different rootstocks (MM-106, Marubakaido and Marubakaido with M-9 interstock) were stored for eight months in two CA conditions (1.2kPa of O2 + <0.5kPa of CO2 and 1.2kPa of O2 + 2.0kPa of CO2). Seven days after removall from CA storage, fruits were assessed for ethylene production rate, skin color (h°), flesh penetration force, titratable acidity, soluble solids content, incidence and severity of internal breakdown and mineral composition (Ca, Mg and K) in the fruit pulp. Among the CA conditions, fruits stored in 2 kPa CO2 showed delayed in the ripening compared to fruits stored in <0.5 kPa CO2. When comparing rootstocks, fruits harvested from trees on Marubakaido and Marubakaido with M-9 interstock and then stored in 2.0 kPa of CO2 showed higher incidence of internal breakdown than fruits harvested from trees on MM-106 rootstock. Fruits harvested from trees on MM-106 rootstock had higher Ca and lower K contents, and lower K/Ca ration, than fruits harvested from trees on Marubakaido and Marubakaido with M-9 interstock. Fruit quality of 'Fuji' apples is more affected by the CA storage condition than by rootstock of the trees. Fruits from trees on MM-106 rootstock had lower predisposition to internal breakdown, which in turn is related to the mineral composition of fruit.